The brain dominate among students at University of Benghazi and its relationship to academic specialization (scientific, literary), and gender. (Journal of Human Sciences, 2024)
The study aimed to identify the prevailing pattern of cerebral dominance (Right , Lift ) among students of The  university of Benghazi , faculties ; Literature , Engineering , Medicine , Al-Marj , the study also aimed to identify the relationship of the pattern of brain dominance, according to the variables of academic specialization, and gender , the study also aimed to uncover differences in cerebral dominance patterns attributed to the two variables of gender , and the  academic specialization , and used (HBDI) scale , on a sample of (100) students , (50) students from  faculties Engineering , Medicine (50) students from Literature, the study found the left pattern of cerebral dominance was the most common among students , followed by the Right pattern , and the study also found that there is a relation between the pattern of brain dominance and gender , there is no relationship between the pattern of brain dominance and academic specialization , and there no difference in the pattern of brain dominance due to according to the variables of academic specialization , and gender.